Type VI Secretion System in Pathogenic Escherichia coli: Structure, Role in Virulence, and Acquisition - Navarro-Garcia, Fernando; Ruiz-Perez, Fernando; Cataldi, Ángel; Larzábal, Mariano (Frontiers in Microbiology, 2019)
Bacterial pathogens utilize a myriad of mechanisms to invade mammalian hosts, damage tissue sites, and evade the immune system. One essential strategy of Gram-negative bacteria is the secretion of virulence factors through both inner and outer membranes to reach a potential target. Most secretion systems are harbored in mobile elements including transposons, plasmids, pathogenicity islands and phages, and Escherichia coli is one of the more versatile bacteria adopting this genetic information by horizontal gene transfer. Additionally, E. coli is a bacterial species with members of the commensal intestinal microbiota and pathogens associated with numerous types of infections such as intestinal, urinary and systemic in humans and other animals. T6SS clusters plasticity suggests evolutionarily divergent systems were acquired horizontally. T6SS is a secretion nanomachine that is extended through the bacterial double-membrane; from this apparatus substrates are conveyed straight from the cytoplasm of the bacterium into a target cell or to the extracellular space. This nanomachine consists of three main complexes: proteins in inner membrane that are T4SS components-like, the baseplate complex and the tail complex which are evolutionarily related to contractile bacteriophage tails. Advances in the T6SS understanding include the functional and structural characterization of at least 13-subunits (so-called core components) which are thought to conform the minimal apparatus. So far, the main role of T6SS is on bacterial competition by using it to kill neighboring non-immune bacteria for which anti-bacterial proteins are secreted directly into the periplasm of the bacterial target after cell-cell contact. Interestingly, a few T6SSs have been associated directly to pathogenesis, e.g., roles in biofilm formation and macrophage survival. Here we focus on the advances on T6SS from the perspective of E. coli pathotypes with emphasis in the secretion apparatus architecture, the mechanisms of pathogenicity of effector proteins and the events of lateral gene transfer that led to its spread.